ABCB1/MDR1/P‐gp employs an ATP‐dependent twist‐and‐squeeze mechanism to export hydrophobic drugs. Issue 6 (11th December 2020) - Kodan, Atsushi; Futamata, Ryota; Kimura, Yasuhisa; Kioka, Noriyuki; Nakatsu, Toru; Kato, Hiroaki; Ueda, Kazumitsu
Abstract : ABCB1, also called MDR1 or P‐glycoprotein, exports various hydrophobic compounds and plays an essential role as a protective physiological barrier in several organs, including the brain, testis, and placenta. However, little is known about the structural mechanisms that allow ABCB1 to recognize hydrophobic compounds of diverse structures or the coupling of ATP hydrolysis to uphill substrate export. High‐resolution X‐ray crystal structures of the pre‐ and post‐transport states and FRET analyses in living cells have revealed that an aromatic hydrophobic network at the top of the inner cavity is key for the conformational change in ABCB1 that is triggered by a hydrophobic substrate. ATP binding, but not hydrolysis, induces a progressive network that results in a twisting motion of the whole protein, squeezing out the substrate directly to the extracellular space. This twist‐and‐squeeze mechanism by which ABCB1 exports hydrophobic substrates is distinct from those of other transporters. Abstract :